Public administration in America - Gordon, George J. (New York : St. Martin's Press, 1982)
This book has three principal emphases. The first is on the central importance of public administration in modern government. With literally thousands of separate public programs and hundreds of billions of dollars spent each year in managing them, the scope of administrative operations at all governmental levels is immense. The second emphasis is on the role and impact of politics in shaping public administration. Government agencies are affected by politics, and students should be aware of the many ways in which political interests and administrative organization and practice are intertwined. This book does not take the position that it is necessarily wrong or harmful that politics plays such a prominent role. The discussion of politics is explanatory rather than moralizing; "pros" and "cons" of issues such as government regulation are carefully examined, and the reader is encouraged to draw independent conclusions. The third emphasis is on management aspects of public administration--on concerns relating to the operation of public programs, from the perspective of the public agency manager. Among such concerns are communication and coordination, program planning, collective bargaining with public employees, and--especially since the mid-1970s--the growing "fiscal stress" felt by rising numbers of governments and agencies.
Includes bibliographies and index.
lje
Loan
Keywords: Public administration; Public administration; America